2006
DOI: 10.1109/tsa.2005.858051
|View full text |Cite
|
Sign up to set email alerts
|

Prosody modification using instants of significant excitation

Abstract: Abstract-Prosody modification involves changing the pitch and duration of speech without affecting the message and naturalness. This paper proposes a method for prosody (pitch and duration) modification using the instants of significant excitation of the vocal tract system during the production of speech. The instants of significant excitation correspond to the instants of glottal closure (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
83
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(83 citation statements)
references
References 20 publications
0
83
0
Order By: Relevance
“…With the knowledge of the epochs, it is possible to determine the characteristics of the voice source by a careful analysis of the signal within a glottal pulse. The epochs can be used as pitch markers for prosody manipulation, which is useful in applications like text-to-speech synthesis, voice conversion and speech rate conversion [3], [4]. Knowledge of the epoch locations may be used for estimating the time-delay between speech signals collected over a pair of spatially distributed microphones [5].…”
Section: A Significance Of Epochs In Speech Analysismentioning
confidence: 99%
“…With the knowledge of the epochs, it is possible to determine the characteristics of the voice source by a careful analysis of the signal within a glottal pulse. The epochs can be used as pitch markers for prosody manipulation, which is useful in applications like text-to-speech synthesis, voice conversion and speech rate conversion [3], [4]. Knowledge of the epoch locations may be used for estimating the time-delay between speech signals collected over a pair of spatially distributed microphones [5].…”
Section: A Significance Of Epochs In Speech Analysismentioning
confidence: 99%
“…Thirdly, some neutral sentences had unsatisfactory prosody. The quality was improved by modifying the prosody with algorithms for pitch and duration modification [11] [12], speech normalization and energy correction. Some of these algorithms were integrated into the Festival framework for increased automation.…”
Section: Improvements Made On the Baseline Systemmentioning
confidence: 99%
“…These methods produce some spectral and phase distortions, mainly due to manipulation of the speech signal directly. In [6], the authors have proposed an epoch-based time scale modification method, where the duration of speech signal is modified using the knowledge of epochs. Here, the epoch refers to the instant of glottal closure, where significant excitation takes place in each glottal cycle.…”
mentioning
confidence: 99%
“…In the method proposed in [6], the TSM is performed by modifying the entire speech signal uniformly. In general, it is observed that all speech regions do not change uniformly with changes in the speech rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation